Nest Gasses as a Potential Attraction Cue for Biting Flying Insects and Other Ectoparasites of Cavity Nesting Birds - Castaño-Vázquez, Francisco; Merino, Santiago; Cuezva, Soledad; Sánchez-Moral, Sergio (Frontiers in Ecology and Evolution, 2020)
The presence of nestlings and other nest dwelling living beings in nests built in cavities alter the composition of gases inside the cavity. This different concentration of gases could be used by some parasites as a cue to localize their hosts. Here, we explored the temporal variation in the concentration and isotopic signature of carbon dioxide (CO2) and methane (CH4) inside nest boxes of blue tits Cyanistes caeruleus during the nestling period (days 3, 8, 13, 20 and 21 post-hatching) as well as several variables potentially affecting such variation. Finally, we checked whether difference in gases concentration affects the number of different types of parasites affecting nestlings. Concentration of gases and isotopic signature were significantly different between nest cavities and the forest during the nestling period. CO2 concentration was higher while CH4 was lower inside nests than in forest air. We expect that the abundance of those parasites seeking actively for nests (blackflies, biting midges and blowflies) could be related with differences in gases concentrations if they use these differences as a cue for host location. In this respect, abundance of biting midges were related positively with differences in CO2 between nest and forest at day 20 of nestling age indicating that these mosquitoes can use concentrations of that gas to find their host. In addition, we found a positive relationship between blackflies and differences in CH4 concentration. However, concentration of this gas inside nests may be related with bacterial activity and therefore this relationship may be due to an effect of bacteria on blackflies and not to the effect of gas as a blackfly attractant to nests. Other relationships between difference on gases concentration and mites were found but due to the way these parasites use to reach nests (i.e.: transported by adult birds) we discard the possibility that they use that difference as a cue for host location. Brood size was also related with mite and flea abundances and relative humidity with flea abundance. In addition, the condition of blue tit females was negative and significantly related with the abundance of blowfly pupae.